Use of Moving Average Convergence Divergence for Predicting Price Movements - Joshi, Dushyant Lal (International Research Journal of MMC, 2022)
The main purpose of this study is to carrying out how Moving Average Convergence Divergence (MACD) works for predicting price of securities and to assist investment decisions. It is one of the powerful technical indicators, which is frequently used by technical analysist in stock market. However, most tests fail to verify performance with traditional parameter settings of 12, 26, and 9 days. This technique consists of a combination of close neighbor classification and some well-known tools of technical analysis, namely, stop loss or stop profit. In order to evaluate the potential use of the proposed method in practice, we compare the results obtained with the results obtained by adopting the buy and hold strategy. This paper shows how trade signal generated by this indicator can be used to minimize trading risk in markets. This study also tests which model is able to improve profitability by applying additional criteria to avoid false trade signals. The key performance measure in this technique is profitability. Technical analysis is used to assist in properly timing entry and exit points, when to buy and sell of stocks?